2012
DOI: 10.1097/aog.0b013e318265de39
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Muscle Strength After Childbirth

Abstract: OBJECTIVE The objective was to estimate the effect of vaginal childbirth and other obstetric exposures on pelvic muscle strength 6–11 years after delivery and to investigate the relationship between pelvic muscle strength and pelvic floor disorders. METHODS Among 666 parous women, pelvic muscle strength was measured with a perineometer 6–11 years after delivery. Obstetric exposures were classified by review of hospital records. Pelvic floor outcomes, including stress incontinence, overactive bladder, anal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 23 publications
2
62
1
5
Order By: Relevance
“…In fact, the caesarean group had a longer second stage compared to the vaginal group, A labored cesarean may reflect other factors, such as obstructive labor resulting in cesarean delivery. We found that 25% of cesareans had a decrease in PFS, in line with previous studies showing a decrease in strength in caesareans who labor 4,22 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In fact, the caesarean group had a longer second stage compared to the vaginal group, A labored cesarean may reflect other factors, such as obstructive labor resulting in cesarean delivery. We found that 25% of cesareans had a decrease in PFS, in line with previous studies showing a decrease in strength in caesareans who labor 4,22 .…”
Section: Discussionsupporting
confidence: 92%
“…The reduction of pelvic muscle strength after vaginal delivery compared to cesarean has been reported in multiple studies 7,8,12,22 . The general consensus is that vaginal delivery reduces strength 4,7,8,10,23 . The finding of increasing age significantly impacting PFS reduction is novel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estas são geralmente empregadas como (a) biofeedback da pressão da cavidade vaginal durante o tratamento (43), (b) ferramenta diagnóstica da pressão para diferenciar grupos de pacientes (continentes e incontinentes) (18,44), (c) resposta do sucesso ou não da terapia utilizada (45). Apesar de aparentemente correspondentes e serem ainda usadas na literatura sem distinção apropriada, a dinamometria é uma ferramenta mais sensível, precisa, direta e específica que a perineometria.…”
Section: Avaliação Do Assoalho Pélvicounclassified